Positive practice environments in critical care units in South Africa - Pretorius, R.; Klopper, H.C. (International nursing review, 2012)
PRETORIUS R. & KLOPPER H.C. (2011) Positive practice environments in critical care units in South Africa. International Nursing Review59, 66–72 Background:  The demanding nature of the critical care unit (CCU) presents a challenge to many nursing professionals and carries the risk of a high turnover rate. The critical care nurse (CCN) is responsible for caring for the most ill patients in hospitals, and the acute shortage of nurses contributes to the intensity and pressure of the environment. While the reasons for the nursing shortage are varied and complex; a key factor seems to be an unhealthy work environment. Little evidence exists of research conducted to investigate the practice environment of CCNs in South Africa (SA). Purpose:  This study aimed to construct a grounded theory for positive practice environments (PPEs) in private CCUs in SA. Methods:  Intensive interviews and a constant comparative approach to data collection and data analysis were used to explore the participants' (n = 6) perceptions of the elements of a PPE. Findings:  A theory depicting the core conceptual category of being in control and its relation to the other six categories was constructed from the data to explain a PPE for private CCUs in SA. Conclusions:  The study provides a robust overview of the elements of a PPE and contributes to the constructivist application of grounded theory. Study limitations:  The study was conducted in the private healthcare sector in SA, thus limiting the findings to this context.